PSVII-38 Increased activity in horses following reapplication of shoes. (5th December 2019) - Groux, Rosemary; Whitlock, Brian; Krawczel, Peter D; Lee, Amanda; Daniel, Jay A
Abstract: Despite shoeing being a common practice, the impact of shoeing on horse behavior has not been widely studied. To examine the impact of reapplication of shoes to previously shod horses on horse activity, seven light horse geldings (3 to 21 year old Quarter Horse, Dutch Warmblood, or Thoroughbred) were fitted with three axis accelerometers (IceTag, Ice Robotics, Edinburgh, Scotland) on the left rear leg. Horses were maintained on pasture except for approximately 1 hour morning and evening for feeding. Boots were placed under the accelerometer, and boots and accelerometers were removed once daily for approximately one hour while the horses were stalled for am feeding to examine the horses' leg and to allow exposure to air to dry. After seven days, horses were treated by either having shoes removed, feet trimmed, and new shoes fitted (reapplication; n = 3) or being handled by the farrier but not trimmed or fitted with new shoes (sham; n = 4). Horse activity was then monitored for 6 d. Steps per hour were tested for effects of treatment, time (before or after treatment), and interaction of treatment by time using procedures for repeated measures with JMP Software (version 7, SAS Inst. Inc., Cary, NC). Means separation was performed using Student's t test if appropriate. There was a treatment by time interaction (P = 0.0109), such that after treatment, reapplication horses took more steps than sham horses (150 ± 20 vs 117 ± 18 steps per hour, respectively). However, both groups took fewer steps after treatment than before (124 ± 13 vs 157 ± 13 steps per hour, respectively; P < 0.0001). These results indicate horses with reapplication of shoes move more than horses which did not experience reapplication of shoes, possibly indicated the horses with reapplication of shoes experienced more comfort in movement.